Aktifitas Perasan Daun Pucuk Merah (Syzygium oleana) Sebagai Bahan Alami Hand Sanitizer - Dj, Herlinda Djohan; Sugito, Sugito; Slamet, Slamet (Jurnal Laboratorium Khatulistiwa, 2022)
Indonesia is a country that has a fairly high biodiversity, one of which is red shoots (Syzygium oleana). Red shoots are reported to have strong potential to inhibit bacterial growth, including tannins, saponins, flavonoids, and essential oils. To increase effectiveness in utilizing the potential of red shoots, it is made in a practical and easy-to-use dosage form. One of the effective dosage forms for topical therapy is hand sanitizer. The increasing prevalence of the corona virus has caused a shortage of hand sanitizers. Until now, there is no treatment that can cure Corona virus infection. Therefore, the World Health Organization (WHO) appeals to take preventive measures, one of which is washing hands properly. ThisÂ  study aimedÂ  to examine the antibacterial potential of red shoots (Syzygium oleana) against the growth of Staphylococcus aureus bacteria using the disc method. The juice is made in the form of a Hand Sanitizer Spay. The antibacterial activity was obtained by measuring the diameter of the inhibition zone after giving 4 variations of the concentration of the juice sample. Positive control used amoxicillin 30 g/disk and negative control used aquadest. The next stage of analysis of the quality of hand sanitizers includes organoleptic tests, pH measurements. The research design used is a quasi-experimental method. This research was started in May-December 2022. Samples in the form of red shoots were made in the form of Hand Sanitizer Spay with various concentrations of 5%, 10%, 15%, and 20% and the average inhibition zone value was 11.8 mm, 12.6 mm, 13.75 mm and 14.4 mm. Based on the results of research and computerized data processing with the Simple Linear Regression test, the value of p = 0.000 (p <0.05) means that there is an effect of the concentration of hand sanitizer squeezed from red shoots on the inhibition of Staphylococcus aureus bacteria.